2008
DOI: 10.1074/jbc.m804604200
|View full text |Cite
|
Sign up to set email alerts
|

Whi3, a Developmental Regulator of Budding Yeast, Binds a Large Set of mRNAs Functionally Related to the Endoplasmic Reticulum

Abstract: Whi3 is an RNA-binding protein associated with the endoplasmic reticulum (ER) that binds the CLN3 mRNA and plays a key role in the efficient retention of cyclin Cln3 at the ER. In the present work, we have identified new Whi3-associated mRNAs by a genomic approach. A large and significant number of these Whi3 targets encode for membrane and exocytic proteins involved in processes such as transport and cell wall biogenesis. Consistent with the genomic data, we have observed that cell wall integrity is compromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 51 publications
(64 reference statements)
5
87
1
Order By: Relevance
“…The RRM of Whi3 would bind the CLN3 mRNA and restrict Cln3 synthesis in the endoplasmic reticulum (3,4,6,7). Here, we showed that PKA phosphorylated Ser-568 of this RRM, thus inhibiting Whi3 function.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The RRM of Whi3 would bind the CLN3 mRNA and restrict Cln3 synthesis in the endoplasmic reticulum (3,4,6,7). Here, we showed that PKA phosphorylated Ser-568 of this RRM, thus inhibiting Whi3 function.…”
Section: Discussionmentioning
confidence: 84%
“…Whi3 function is important not only for control of the G 1 /S transition but also for the switch to developmental options such as invasive growth and meiosis (3,4,6,7). None of the above studies addressed the role of the phosphorylation of Whi3 in such cellular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we determined the influence of Whi3 on the protein/mRNA ratio of selected biofilm regulators including components of the cAMP-PKA pathway (Tpk1, Tpk2, and Flo8), the PKA-regulated Yak1 branch (Yak1 and Phd1), and the Fus3/Kss1 MAPK cascade (Tec1) as well as the RNA-binding protein Mpt5. We also included Mig2, which has not been associated with biofilm formation, but whose mRNAs are bound by Whi3 in vivo (Colomina et al 2008).…”
Section: Whi3 Controls Key Regulators Of Yeast Development At the Posmentioning
confidence: 99%
“…For this purpose, we determined the influence of Whi3 on the protein/mRNA ratio of selected biofilm regulators including components of the cAMP-PKA pathway (Tpk1, Tpk2, and Flo8), the PKA-regulated Yak1 branch (Yak1 and Phd1), and the Fus3/Kss1 MAPK cascade (Tec1) as well as the RNA-binding protein Mpt5. We also included Mig2, which has not been associated with biofilm formation, but whose mRNAs are bound by Whi3 in vivo (Colomina et al 2008).To determine the effect of Whi3 on production of these regulators, we used the same experimental approach as for the analysis of G 1 cyclins and created a series of WHI3 and whi3Δ yeast strains that carry endogenous fusions of corresponding genes to GFP. Resulting strains were assayed for biofilm formation, showing that all fusion genes are fully functional except FLO8-GFP that conferred partially reduced functionality ( Figure S1).…”
mentioning
confidence: 99%